Digital rehabilitation for prisoners: A utilitarian approach - Muhammad Oscar Dharma Putra Mulya (Education of Law Journal, 2025)
This research aims to review the implementation of the concept of digital rehabilitation as a model of prisoner rehabilitation to support the reintegration of prisoners into digital society from a utilitarian perspective, in particular by using Jeremy Bentham and John Stuart Mill’s theory of utilitarianism. The purpose of digital rehabilitation is to leverage the efficiency of prisoner rehabilitation by utilizing digital technologies. Such efficiency can be measured by the success of prisoner reintegration, in which one of the indicators is the reduction of the recidivism rate. The idea of digital rehabilitation is relevant to be considered based on the social fact that correctional institutions in Indonesia are experiencing overcrowding situation, and one of the contributing factors is the high number of recidivists. On the other hand, the currently applied Law Number 22/2022 on Correctional Institution does not recognize the concept of digital rehabilitation, which illustrates the legal gap between the law and the development of science and technology. This research is classified as normative research conducted by integrating philosophical and conceptual approaches. The result of this research shows that digital rehabilitation benefits not just prisoners for supporting their reintegration, but also society as a whole for creating a safer environment. In other words, the incorporation of the digital rehabilitation concept in statutory regulation is in line with the essence of the utilitarian theory, that is to realize “the greatest happiness for the greatest number”, and also to serve as a means to resolve the issue of correctional institution overcrowding in Indonesia.